Penggunaan Nama yang Berbeda pada Akad Nikah dan Buku Nikah Perspektif Hukum Islam dan Hukum Positif - Awwalia, Risnanda Anandari; Ulya, Zakiyatul (Department of Comparative Mazhab Comparative, Fakulty of Shariah and Law, 2024)
Abstract: Marriage is a sacred institution regulated by both Islamic law and positive law. Despite these regulations, marriage practices often involve cultural customs, such as using different names during the wedding ceremony at the Rembang District KUA. People frequently request to be married under a name different from their official documentation. This raises an interesting question for examination: the practice of marriage with different names at the KUA and the analysis of the validity of such marriages under Islamic law and positive law. This research employs field research methods with a qualitative approach. Data was collected through interviews and documentation. The collected data is analysed deductively. The results indicate that marriages with different names at the Rembang District KUA follow the marriage registration procedures, from registration to the issuance of the marriage certificate, with the difference lying in the use of names. Local customs, concerns about marital failure, the desire for a harmonious family, and permission from the KUA influence the use of different names. This practice does not conflict with Islamic law because the pillars and conditions of marriage are fulfilled, making the marriage valid under Islamic law. However, this practice contradicts positive law, specifically PMA Number 20 of 2019 concerning Marriage Registration, due to inconsistencies between the names used in the ceremony and those recorded.Keywords: Validity of Marriage; Different Names; Islamic Law; Positive Law. Abstrak: Perkawinan adalah sesuatu yang sakral yang diatur dalam hukum Islam dan hukum positif. Meskipun sudah diatur, praktik perkawinan sering melibatkan budaya masyarakat, seperti penggunaan nama berbeda saat akad nikah di KUA Kecamatan Rembang. Masyarakat sering meminta dinikahkan dengan nama yang berbeda dari dokumen kependudukannya. Hal ini menimbulkan pertanyaan yang menarik untuk dikaji, yaitu terkait praktik perkawinan dengan nama berbeda di KUA tersebut serta keabsahan perkawinan ini dalam pandangan hukum Islam dan hukum positif. Penelitian ini merupakan penelitian lapangan dengan pendekatan kualitatif. Data dikumpulkan melalui wawancara dan dokumentasi. Data yang terkumpul dianalisis seacra deduktif. Hasil penelitian menunjukkan bahwa perkawinan dengan nama berbeda di KUA Kecamatan Rembang mengikuti prosedur pencatatan nikah, mulai dari pendaftaran hingga penyerahan buku nikah, dengan perbedaan terletak pada penggunaan nama. Penggunaan nama berbeda tersebut dilatarbelakangi oleh adat yang berlaku di masyarakat, kekhawatiran kegagalan rumah tangga, keinginan keluarga harmonis, serta izin dari KUA. Praktik ini tidak bertentangan dengan hukum Islam karena rukun dan syarat perkawinan terpenuhi, sehingga sah menurut hukum Islam. Namun, praktik ini tidak sejalan dengan hukum positif, khususnya PMA Nomor 20 Tahun 2019 tentang Pencatatan Pernikahan, karena terdapat ketidaksesuaian antara nama yang digunakan dalam pelaksanaan dan pencatatan.Kata Kunci: Keabsahan Perkawinan; Nama berbeda; Hukum Islam; Hukum Positif.